Змістовний компонент формування конфліктологічної культури майбутніх слідчих ОВС у фаховій підготовці - Гіренко, С. П.; Girenko, S. P.; Сергій Гіренко (Вісник Національного університету оборони України. - 2013. - Вип. 6. - С. 42-47, 2013)
В статті розглянуто різні аспекти професійної конфліктологічної підготовки майбутніх працівників слідчих підрозділів ОВС в педагогічному процесі. Окреслено сучасний стан та особливості конфліктологічної сфери у підрозділах слідства МВС, визначені конфліктогени професійного середовища органів внутрішніх справ.

In the article deals with various aspects of the professional preparation of future employees conflictological investigative units of militia in the pedagogical process. Outlines the current status and characteristics of conflictological areas in investigative units of militia identified conflictogens professional environment of the Interior. The author analyzed scientific publications that explore contemporary issues conflictological preparation of future professionals in higher education . Determine the relevance and breadth offeatures manifestation of conflict in the investigative activities. Consider the sphere of conflict relations investigator with various parties to the proceedings. Attention is given to departmental documents forming the non-conflict moral obligations and standards of conduct of police officers. The author offers advice on the psychological behavior of investigators in the conflict.

В статье рассмотрены различные аспекты профессиональной конфликтологической подготовки будущих работников следственных подразделений ОВД в педагогическом процессе. Очерчены современное состояние и особенности конфликтологической сферы в следственных подразделениях МВД, определены конфликтогены профессиональной среды органов внутренних дел.
Содержательный компонент формирования конфликтологической культуры будущих следователей ОВД в профессиональной подготовке
Substantial component of forming of conflictological culture of the future of investigative units in professional preparation
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; курсанти; курсанты; cadets; вищі навчальні заклади Міністерства внутрішніх справ України; высшие учебные заведения Министерства внутренних дел Украины; higher educational establishments within the system of the Ministry of Internal Affairs of Ukraine; конфлікт; конфліктологічна культура; слідча діяльність; професійна освіта; конфликт; конфликтологическая культура; следственная деятельность; профессиональное образование; conflict; conflictological culture; investigative activity; vocational education